Inheritance of Feitiao Cultural Heritage Through Virtual Reality Technology to Design Cultural Dynamics for Generation Z of the Maonan People, Guangxi Zhuang Autonomous Region, People’s Republic of China: Inheritance of Feitiao Cultural Heritage Through Virtual Reality Technology to Design Cultural Dynamics for Generation Z of the Maonan People, Guangxi Zhuang Autonomous Region, People’s Republic of China - Qin, Su; Lertrujidumrongkul, Pradiphat; Kaewsaisoon , Wanchai (RATANABUTH JOURNAL, 2026)
This study aimed to (1) examine the historical background and cultural symbols of the Feitao ritual among the Maonan ethnic group, (2) develop cultural intellectual property (IP) characters aligned with Generation Z preferences, and (3) apply Augmented Reality (AR) technology to design interactive experiences for cultural heritage transmission. A mixed-methods approach was employed, integrating qualitative data from document analysis and in-depth interviews with quantitative data collected from a sample of 200 participants, including Generation Z individuals and community stakeholders. Research instruments included semistructured interviews and questionnaires. Qualitative data were analyzed using content analysis, while quantitative data were analyzed using descriptive statistics, including mean and standard deviation. The findings revealed that key cultural symbols of the Feitao tradition, particularly Nuo masks and ritual performances, can be effectively transformed into distinctive cultural IP characters that resonate with Generation Z audiences. The application of AR technology significantly enhanced user engagement and interaction, with overall satisfaction reported at a high level (= 3.39, S.D. = 1.00). Furthermore, the integration of cultural symbolism with digital technology demonstrates strong potential for developing innovative models of cultural heritage transmission in contemporary society. In conclusion, the integration of AR technology with cultural intellectual property design represents an effective and innovative approach to preserving and transmitting intangible cultural heritage to younger generations.